NEED OF THE HOUR: ADDRESSING LIGHT POLLUTION (International Journal of Food and Nutritional Sciences, 2023)
Light pollution, an often-overlooked environmental issue, significantly impacts ecosystems, human health, and astronomical observations. This paper examines the causes, effects, and solutions to light pollution, emphasizing the urgent need for global intervention. Using seven tables to illustrate data and strategies, the study aims to provide a comprehensive understanding of this growing problem.